SPECTROSCOPIC ANALYSIS OF A COMPOUND ISOLATED FROM THE ETHYL ACETATE FRACTION OF CALOPHYLLUM MACROPHYLLUM SCHEFF AND TOXICITY TESTS USING THE BSLT METHOD AGAINST ARTEMIA SALINA LEACH LARVAE - Noni Zakiah; M Munira; Rini Handayani; R Rasidah; F Frengki (Universitas Syiah Kuala, 2022)
The Calophyllum genus has been reported to be rich in bioactive compounds that have medicinal properties. The author will also report the results of the isolation of compounds obtained from the ethyl acetate fraction of the bark of the plant C. macrophyllum Scheff, a type of Calophyllum found in Mount Kerinci, Jambi province. This paper will analyze the spectroscopic data of these compounds which include UV, IR, GC-MS, 1HNMR and 13CNMR spectra which are amplified by HMQC and HMBC spectra. The first step in bioactivity testing is the toxicity test using the BSLT (Brine Shrimp Lethality Test) method using Artemia Salina Leach shrimp larvae. The results of the spectroscopic analysis obtained the chemical formula as a derivative of fatty acid methyl ester (methyl-octadec-14 enoic), in the form of a yellow liquid with a boiling point of 173-175°C. The results of the initial screening for bioactivity through the toxicity test of the BSLT method on Artemia salina Leach shrimp larvae obtained an LC50 value of 141.2 g/mL. This compound still has the potential to have certain bioactivity